2002
DOI: 10.1046/j.1432-1033.2002.03051.x
|View full text |Cite
|
Sign up to set email alerts
|

Conformational analysis by CD and NMR spectroscopy of a peptide encompassing the amphipathic domain of YopD from Yersinia

Abstract: To establish an infection, Yersinia pseudotuberculosis utilizes a plasmid-encoded type III secretion machine that permits the translocation of several anti-host factors into the cytosol of target eukaryotic cells. Secreted YopD is essential for this process. Pre-secretory stabilization of YopD is mediated by an interaction with its cognate chaperone, LcrH. YopD possesses LcrH binding domains located in the N-terminus and in a predicted amphipathic domain located near the C-terminus. This latter domain is also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 53 publications
2
24
0
Order By: Relevance
“…The full-length and Nterminal binding regions of YopD are insoluble and in vitro biophysical characterization has not been achieved. To the contrary, the C-terminal YopD 278-292 peptide is readily soluble and forms an amphipathic a-helix in solution [18]. The binding site of YopD was postulated to localize to a large surface on the model of SycD, the opposite side of the YopB interactions [19], in agreement with data for a common chaperone of YopD and YopB [16].…”
supporting
confidence: 72%
See 1 more Smart Citation
“…The full-length and Nterminal binding regions of YopD are insoluble and in vitro biophysical characterization has not been achieved. To the contrary, the C-terminal YopD 278-292 peptide is readily soluble and forms an amphipathic a-helix in solution [18]. The binding site of YopD was postulated to localize to a large surface on the model of SycD, the opposite side of the YopB interactions [19], in agreement with data for a common chaperone of YopD and YopB [16].…”
supporting
confidence: 72%
“…Overall, the behavior is consistent with a partially unfolded peptide. The YopD 150-287 peptide contains the first 10 residues of the region proposed to bind the SycD chaperone [18]. It was of interest to investigate if the truncated region was sufficient to bind the SycD chaperone in a stable complex.…”
Section: Resultsmentioning
confidence: 99%
“…Site-directed Mutagenesis of the YopD C Terminus-Phenotypic analysis of YopD variants lacking a putative coiled-coil domain between residues 248 and 277 (36) and the amphipathic domain encompassing residues 278-292 (35,49) suggested that both features were central to YopD-mediated effector delivery into eukaryotic cells (9,11). Furthermore, the hydrophobic residues on one side of the amphipathic ␣-helix primarily contributed to an interaction with the cognate chaperone LcrH (37) and subsequent yop regulatory control (28,29).…”
Section: Resultsmentioning
confidence: 99%
“…Such a role is known for the C-terminal amphipathic domain (Tengel et al, 2002), which is essential for Yop effector translocation (Francis & Wolf-Watz, 1998). Interestingly, a helical wheel projection (ANTHEPROT version 3.2; G. Deleage, France) over the equivalent region in PopD only predicted an a-helix with marginal amphipathic properties (data not shown).…”
Section: Discussionmentioning
confidence: 98%